This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since sin ( α ) = 2 sin ( 2 α ) cos ( 2 α ) , if we divide both the numerator and denominator of the given expression by cos 2 ( 2 α ) the expression becomes
sec 2 ( 2 α ) + 2 tan ( 2 α ) sec 2 ( 2 α ) − 2 tan 2 ( 2 α ) = tan 2 ( 2 α ) + 2 tan ( 2 α ) + 1 1 − tan 2 ( 2 α ) ,
where the identity sec 2 ( x ) = tan 2 ( x ) + 1 was used. The expression can now be factored as
( 1 + tan ( 2 α ) ) 2 ( 1 − tan ( 2 α ) ) ( 1 + tan ( 2 α ) ) = 1 + tan ( 2 α ) 1 − tan ( 2 α ) = 1 + k 1 − k , assuming sin ( α ) = − 1 .